How does monetary policy affect income and wealth inequality? Evidence from quantitative easing in the euro area - Michele Lenza; Jirka Slacalek (European Central Bank (ECB), 2018)
This paper studies the effects of quantitative easing on income and wealth of individual euro area households. The aggregate effects of quantitative easing are estimated in a multi-country VAR model of the four largest euro area countries, in which key variables affecting household income and wealth are included, such as the unemployment rate, wages, interest rates, house prices and stock prices. The aggregate effects are distributed across the individual households by means of a reduced-form simulation on micro data from the Household Finance and Consumption Survey, capturing the income composition, the portfolio composition and the earnings heterogeneity channels of transmission. We find that the earnings heterogeneity channel plays a key role: quantitative easing compresses the income distribution since many households with lower incomes become employed. In contrast, monetary policy has only negligible effects on wealth inequality.
Keywords: D14; D31; E44; E52; E58; 330; Monetary Policy; Household Heterogeneity; Inequality; Income; Wealth; Quantitative Easing; Great Recession